If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = -6x + 5x + 4 Reorder the terms: -1 = 4 + -6x + 5x Combine like terms: -6x + 5x = -1x -1 = 4 + -1x Solving -1 = 4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1 + x = 4 + -1x + x Combine like terms: -1x + x = 0 -1 + x = 4 + 0 -1 + x = 4 Add '1' to each side of the equation. -1 + 1 + x = 4 + 1 Combine like terms: -1 + 1 = 0 0 + x = 4 + 1 x = 4 + 1 Combine like terms: 4 + 1 = 5 x = 5 Simplifying x = 5
| -7x=11 | | -100=-2+7(4n+6x) | | (X+0.7)(x+3.4)=0 | | (x+1)(4x-3)=2(x+1)(2x+3) | | 12600-s=925 | | 8x+8+6x+6=56 | | 4x-4=-8x+8x | | 4y-2=6(y+1) | | 0.35x+0.10(260-x)=43.5 | | 7x+3+7x+4=105 | | 3x+2+6x+9=92 | | x-6x+21=76 | | 3(x+2)+4=13 | | -5(n+7)=-115 | | 4(7-3y)+3y=13 | | 3c=13+9c | | X-2-(x+3)=2(x-4)-5 | | 8=-12-5q | | 14=2(1s+15) | | 1-3x=7x | | -5(7x-7)=140 | | 5[x+4]-4x=18-23 | | x^2-2x=54 | | 9=z-[-5] | | -33=9x+3 | | 7(7k+6)=91 | | -4y=-52 | | 15k=-120 | | -88=4(-7-3x) | | 3(X+6)-7=11 | | 66=2l+2*7 | | -(7z+10)=5z |